P19 Father involvement and attitudes in early child-rearing and depressive symptoms in the pre-adolescent period in a uk birth cohort. (2nd September 2017) - Opondo, C; Redshaw, M; Quigley, M
Abstract : Background: Although much of the research on the influence of parenting on child development has emphasised the mother's role, increasing evidence highlights the important role of fathers in the development, health and well-being of their children. In this study we aimed to investigate the association between father involvement in early child upbringing and depressive symptoms in the same children in their pre-teenage years. Methods: Data for the study came from the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort from the southwest of England. The outcome, depressive symptoms, was measured using the short Moods and Feelings Questionnaire (sMFQ) when the children were 9 and 11 years of age. The primary exposure was paternal involvement measured using scores derived from factor analysis of fathers' report of their participation in, understanding of, and feelings about their child's early upbringing. Results: Three factors were identified in the factor analysis. Scores on factor 1 measured fathers' emotional response to the child; scores on factor 2 measured the frequency of fathers' involvement in domestic and childcare activities; scores on factor 3 measured fathers' feelings of security in their role as parent and partner. Children of fathers with high scores on factors 1 and 3 had 12% (OR 0.88, 95% CI 0.81–0.97, p=0.009) and 9% (OR 0.91, 95% CI 0.82–1.00, p=0.040) respectively lower adjusted odds of reporting more depressive symptoms at 9 years. There was no evidence of a difference in depressive symptoms associated with factor 1 and factor 3 scores at 11 years. However, there was weak evidence of a 13% increase in odds of reporting more depressive symptoms associated with 1 unit increase in factor 2 scores at age 9 years (OR 1.13, 95% CI 0.99–1.29, p=0.061) and a 16% increase at 11 years (OR 1.16, 95% CI 1.01–1.34, p=0.040). Conclusion: Positive psychological and emotional aspects of father involvement in children's early upbringing, but not the quantity of direct involvement in childcare, may protect children against developing symptoms of depression in their pre-teen years.